Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
5: \(=\left(1+2+3+4-3-2-1\right)+\left(-\dfrac{1}{2}-\dfrac{2}{3}-\dfrac{3}{4}-\dfrac{1}{4}-\dfrac{1}{3}-\dfrac{1}{2}\right)\)
\(=4+\left(-1-1-1\right)=4-3=1\)
6: \(=\dfrac{25-49}{35}-\left[\dfrac{1}{2}+\dfrac{2}{7}+\dfrac{1}{10}\right]\)
\(=\dfrac{-24}{35}-\dfrac{35+20+7}{70}\)
\(=\dfrac{-24}{35}-\dfrac{62}{70}=\dfrac{-48-62}{70}=-\dfrac{110}{70}=-\dfrac{11}{7}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
3) \(\dfrac{2}{3}-\left(-\dfrac{1}{4}\right)+\dfrac{3}{5}-\dfrac{7}{45}-\left(-\dfrac{5}{9}\right)+\dfrac{1}{12}+\dfrac{1}{90}\)
= \(\dfrac{2}{3}+\dfrac{1}{4}+\dfrac{3}{5}-\dfrac{7}{45}+\dfrac{5}{9}+\dfrac{1}{12}+\dfrac{1}{90}\)
= \(\left(\dfrac{2}{3}+\dfrac{3}{5}-\dfrac{7}{45}+\dfrac{5}{9}+\dfrac{1}{90}\right)+\left(\dfrac{1}{4}+\dfrac{1}{12}\right)\)
= \(\left(\dfrac{60}{90}+\dfrac{54}{90}-\dfrac{14}{90}+\dfrac{50}{90}+\dfrac{1}{9}\right)+\left(\dfrac{4}{12}+\dfrac{1}{12}\right)\)
= \(\dfrac{151}{90}+\dfrac{1}{3}=\dfrac{151}{90}+\dfrac{30}{90}=\dfrac{181}{90}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
9:
\(=5+\dfrac{1}{5}-\dfrac{2}{9}-2+\dfrac{1}{23}+\dfrac{73}{35}-\dfrac{5}{6}-8-\dfrac{2}{7}+\dfrac{1}{18}\)
\(=\left(5-2-8\right)+\left(\dfrac{1}{5}+\dfrac{73}{35}-\dfrac{2}{7}\right)+\left(-\dfrac{2}{9}+\dfrac{1}{18}-\dfrac{5}{6}\right)+\dfrac{1}{23}\)
\(=\left(-5\right)+\dfrac{7+73-10}{35}+\dfrac{-4+1-15}{18}+\dfrac{1}{23}\)
\(=-5+2-1+\dfrac{1}{23}=-4+\dfrac{1}{23}=-\dfrac{91}{23}\)
10: \(=\left(\dfrac{1}{3}+\dfrac{3}{5}+\dfrac{1}{15}\right)+\left(\dfrac{-3}{4}-\dfrac{2}{9}-\dfrac{1}{36}\right)+\dfrac{1}{64}\)
\(=\dfrac{5+9+1}{15}+\dfrac{-27-8-1}{36}+\dfrac{1}{64}\)
=1/64
![](https://rs.olm.vn/images/avt/0.png?1311)
7: \(=\dfrac{-12}{7}\cdot15+\dfrac{2}{7}\cdot\left(-15\right)+\left(-105\right)\cdot\dfrac{70-84+15}{105}\)
\(=\dfrac{-12\cdot15+2\cdot\left(-15\right)}{7}-1\)
\(=\dfrac{-15\cdot14}{7}-1=-15\cdot2-1=-31\)
8: \(=\dfrac{13}{29}\cdot\dfrac{29}{5}-\dfrac{13}{29}\cdot\dfrac{45}{8}-\dfrac{45}{8}\cdot\dfrac{9}{8}+\dfrac{45}{8}\cdot\dfrac{13}{29}\)
\(=-\dfrac{1193}{320}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
13: \(=\dfrac{4}{9}\cdot\left(-7\right)+\left(6+\dfrac{5}{9}\right)\cdot\left(-7\right)\)
\(=\left(-7\right)\left(\dfrac{4}{9}+6+\dfrac{5}{9}\right)=\left(-7\right)\cdot7=-49\)
14: \(=\left(\dfrac{-3}{4}+\dfrac{5}{13}\right)\cdot\dfrac{7}{2}-\left(\dfrac{9}{4}+\dfrac{8}{13}\right)\cdot\dfrac{7}{2}\)
\(=\dfrac{7}{2}\left(-\dfrac{3}{4}+\dfrac{5}{13}-\dfrac{9}{4}-\dfrac{8}{13}\right)\)
\(=\dfrac{7}{2}\left(-3-\dfrac{3}{13}\right)=\dfrac{7}{2}\cdot\dfrac{-42}{13}=\dfrac{-147}{13}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
11: \(=\dfrac{-5}{7}+\dfrac{5}{67}+\dfrac{13}{30}+\dfrac{1}{2}-\dfrac{11}{6}+\dfrac{17}{14}+\dfrac{2}{5}\)
\(=\left(\dfrac{-5}{7}+\dfrac{1}{2}+\dfrac{17}{14}\right)+\left(\dfrac{13}{30}-\dfrac{11}{6}+\dfrac{2}{5}\right)+\dfrac{5}{67}\)
\(=\dfrac{-10+7+17}{14}+\dfrac{13-55+12}{30}+\dfrac{5}{67}\)
\(=1-1+\dfrac{5}{67}=\dfrac{5}{67}\)
12: \(=\dfrac{-1}{4}\cdot\dfrac{152}{11}-\dfrac{1}{4}\cdot\dfrac{68}{11}\)
\(=\dfrac{-1}{4}\left(\dfrac{152}{11}+\dfrac{68}{11}\right)=-\dfrac{1}{4}\cdot20=-5\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1. \(A=\dfrac{2\left(\dfrac{1}{5}+\dfrac{1}{7}-\dfrac{1}{9}-\dfrac{1}{11}\right)}{4\left(\dfrac{1}{5}+\dfrac{1}{7}-\dfrac{1}{9}-\dfrac{1}{11}\right)}=\dfrac{2}{4}=\dfrac{1}{2}\)
2. \(B=\dfrac{1^2.2^2.3^2.4^2}{1.2^2.3^2.4^2.5}=\dfrac{1}{5}\)
3.\(C=\dfrac{2^2.3^2.\text{4^2.5^2}.5^2}{1.2^2.3^2.4^2.5.6^2}=\dfrac{125}{36}\)
4.D=\(D=\left(\dfrac{4}{5}-\dfrac{1}{6}\right).\dfrac{4}{9}.\dfrac{1}{16}=\dfrac{19}{30}.\dfrac{1}{36}=\dfrac{19}{1080}\)
3) \(58\left(3\dfrac{1}{29}-2\dfrac{1}{58}\right):\dfrac{1}{3}\)
\(=58\left(\dfrac{88}{29}-\dfrac{117}{58}\right)\cdot3\\ =\left(58\cdot\dfrac{88}{29}-58\cdot\dfrac{117}{58}\right)\cdot3\)
\(=\left(176-117\right)\cdot3\\ =59\cdot3\\ =177\)
4) \(A=1\dfrac{1}{2}\cdot1\dfrac{1}{3}\cdot1\dfrac{1}{4}\cdot1\dfrac{1}{5}\)
\(=\dfrac{3}{2}\cdot\dfrac{4}{3}\cdot\dfrac{5}{4}\cdot\dfrac{6}{5}\\ =\dfrac{3\cdot4\cdot5\cdot6}{2\cdot3\cdot4\cdot5}\\ =\dfrac{6}{2}\\ =3\)